2019
DOI: 10.1002/14651858.cd001233.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical methods for induction of labour

Abstract: BackgroundMechanical methods were the first methods developed to ripen the cervix and induce labour. During recent decades they have been substituted by pharmacological methods. Potential advantages of mechanical methods, compared with pharmacological methods may include reduction in side effects that could improve neonatal outcomes. This is an update of a review first published in 2001, last updated in 2012.ObjectivesTo determine the effectiveness and safety of mechanical methods for third trimester (> 24 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
137
2
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(158 citation statements)
references
References 253 publications
(765 reference statements)
4
137
2
15
Order By: Relevance
“…Adverse effects, such as uterine hyperstimulation without FHR changes, were also shown to decrease with combined use, as was with this study. There was also no increase in chorioamnionitis and endometritis rates in the Cochrane review [1]. However, it is important to keep in mind that all mechanical methods were included, such as laminaria tents, extra-amniotic infusion in addition to Foley catheters, and so the two studies cannot be directly compared.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Adverse effects, such as uterine hyperstimulation without FHR changes, were also shown to decrease with combined use, as was with this study. There was also no increase in chorioamnionitis and endometritis rates in the Cochrane review [1]. However, it is important to keep in mind that all mechanical methods were included, such as laminaria tents, extra-amniotic infusion in addition to Foley catheters, and so the two studies cannot be directly compared.…”
Section: Discussionmentioning
confidence: 96%
“…There are two main methods of cervical ripening. One is mechanical, including (1) the introduction of a catheter through the cervix into the extra-amniotic space with balloon insufflation; (2) introduction of laminaria tents, or their synthetic equivalent (Dilapan), into the cervical canal; (3) use of a catheter to inject fluid into the extra-amniotic space (EASI), and the other is pharmacological [1,7,8,14,15,[26][27][28][29][30]. Intracervical Foley catheter is the most common mechanical method that was first described by Embrey and Mollison in 1967, where a Foley is inserted into the cervical canal and dilated just past the internal os with mild traction outward dilating the cervix directly, as well as indirectly stimulating prostaglandin (PG) and oxytocin secretion [31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is limited evidence as to which induction methods are preferred by women or the interventions that are most effective and safe to use in outpatient settings [2]. A Cochrane review reported that mechanical methods (trans-cervical balloon catheter) of cervical ripening for IOL are as effective as vaginal prostaglandin PGE 2 [3]. The UK Database of Uncertainties about the Effects of Treatments (UK DUETs) identified mechanical methods of labour induction as a known uncertainty and recommended that future studies on mechanical methods for IOL should have larger sample sizes and report on substantive outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it would be beneficial to compare outpatient outcomes of prostaglandin treatment with 3 concluded that future research could be focused more on safety aspects for the neonate and maternal satisfaction.…”
Section: Introductionmentioning
confidence: 99%